Clinical e radiographic sucess of indirect pulp capping with partial excavation of demineralization dentin in primary posterior teeth - Roberta Francisca Martins de Castro; Ramiro Borba Porto; Marcela Oliveira da Silva; Diana Carla Soares Cunha (Faculdade São Leopoldo Mandic, 2009)
Objective: To assess the outcome of the indirect pulp capping technique after incomplete excavation of the demineralized dentin in primary molars of patients treated in the period from 2004 to 2006.Methods: Sample consisted of 81 teeth of 36 patients aged from 1-to-8 year-old. Clinical and radiographic inclusion criteria, as well as criteria of the success of the evaluated treatments were established.Results: There were four (4.9%) failures and 77 (95.1%) successful treatments. Treatment failure occurred in three girls and in one boy, and no statistically significant difference (p=0.341) was found. Twenty three teeth were treated with resin-modified glass-ionomer cement and 58 with composite resin, of which 22 and 55, respectively, showed successful results. There was no statistically significant difference between restorative materials used (p=0.877). As regards the studied age group, patients aged from 1 to 4 years showed a significantly lower success rate when compared with 5-8 year-old children (p = 0.0428). Conclusion: The results suggest that the indirect pulp capping technique after incomplete excavation of demineralized dentin is a reliable technique to be adopted in deep lesions of primary teeth.